THE IMPACT OF FRANCHISOR SUPPORT ON FRANCHISEE SURVIVAL - Nurul Faizah Halim; Zuraimi Abdul Aziz; Nor Hafiza Othman; Nurul Ashykin Abd Aziz (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
The franchise sector has contributed significantly to economic growth and development. Yet, franchisee resilience compared to independent business is still debatable. The escalation of franchise failure rates during the COVID-19 pandemic has forced the franchise industry to look forward to a long-term survival strategy that ensures a crisis-resistant franchisee model, which is in dire need of business viability and sustainability. Business-to-business franchisor support is part of franchisee continuity’s strategic resources and strategy to steer the business from potential pitfalls. We seek to explore the impact of franchising alliances on franchisee survival during the pandemic crisis. The present study employs the method of structural equation modelling to offer an essential empirical finding on the survival of franchisees within a pandemic recession context linking franchisor support, namely social interaction, service support, financial assistance, assurance, and competence. A survey instrument was employed to gather data from a sample comprising 198 Malaysian franchisees via purposive sampling. Franchisor service support has been found to have a significant impact on franchisee resilience and ability to escape business death and sustain the franchising system. Hence, the study fills the gap in understanding the adequate business-to-business support that franchisees received during the recession that assisted their resilience capability.